PELAKSANAAN PROGRAM PENINGKATAN KINERJA GURU DI MTS NEGERI 3 MEDAN - Syahputra, Muhammad Rizki (Universitas Islam Negeri Sumatera Utara Medan, 2021)
The purpose of this paper is to 1) Analyze the Academic Supervision Implementation Program in Improving Teacher Performance, 2) Analyzing the Teacher Competency Test Implementation Program in Improving Teacher Performance, 3) Analyzing the Teacher Performance Assessment Implementation Program in Madrasahs. The method used is descriptive analytical method, where the researcher will describe, then analyze in depth the research findings. The results of this study are 1) Academic Supervision Implementation Program in Improving Teacher Performance, Coaching for classroom teachers is carried out in three competency areas, namely: a) Academic supervision competence, b) Education supervision competence, and c) Development research competence, 2) Implementation Program Teacher Competency Test in Teacher Performance Improvement, UKG to be able to develop and demonstrate the full competence of a teacher. Complete competence which includes combining and applying a skill, attitude and knowledge that are interrelated, 3) Implementation of Teacher Performance Assessment Program in Madrasah, The teacher performance appraisal process carried out in madrasas follows several provisions, including: (1) The assessment is carried out by the madrasa principal or the deputy head of the madrasa or a competent senior teacher, appointed by the head of the madrasa (who has attended assessment training); (2) The assessment is conducted twice a year (formative assessment at the beginning of the year and summative assessment at the end of the year); (3) The results of the formative assessment are used as the basis for the preparation of profiles and planning of the annual PKB/PKR program for teachers. (4) The results of the summative assessment are used to provide a teacher's work performance value.Program Implementation, Teacher Improvement